Intersatellite Comparisons of GOES Magnetic Field Measurements - Frederick J. Rich; Samuel Califf; Paul T. M. Loto'aniu; Monica Coakley; Alexander Krimchansky; Howard J. Singer (Space Weather)
Abstract GOES‐16 and GOES‐17 are the first of NOAA's Geostationary Operational Environmental Satellite (GOES)‐R series of satellites. Each GOES‐R satellite has a magnetometer mounted on the end (outboard) and one part‐way down a long boom (inboard). This paper demonstrates the relative accuracy and stability of the measurements on a daily and long‐term basis. The GOES‐16 and GOES‐17 magnetic field observations from 2017 to 2020 have been compared to simultaneous magnetic field observations from each other and from the previous GOES‐NOP series satellites (GOES‐13, GOES‐14 and GOES‐15). These comparisons provide assessments of relative accuracy and stability. We use a field model to facilitate the inter‐satellite comparisons at different longitudes. GOES‐16 inboard and outboard magnetometers data suffer daily variations which cannot be explained by natural phenomena. Long‐term‐averaged GOES‐16 outboard (OB) data has daily variations of ±3 nT from average values with one‐sigma uncertainty of ±1.5 nT. Long‐term averaged GOES‐17OB magnetometer data have minimal daily variations. Daily average of the difference between the GOES‐16 outboard or GOES‐17 outboard measurements and the measurements made by another GOES satellite are computed. The long‐term averaged results show the GOES‐16OB and GOES‐17OB measurements have long‐term stability (±2 nT or less) and match measurements from magnetometers on other GOES within limits stated herein. The GOES‐17OB operational offset (zero field value) was refined using the GOES‐17 satellite rotated 180° about the Earth pointing axis (known as a yaw flip).